Anacardium humile como uma nova fonte de moléculas antioxidantes, antiglicantes e inibidoras de α-amilase com potencial para o controle do estresse oxidativo e do diabetes mellitus - Lima Júnior, Joed Pires de (2021)
Diabetes mellitus (DM) is a chronic disease of great medical interest and it has been considered a serious public health problem worldwide. The use of natural products to treat diseases is an ancient practice and can be considered a convenient alternative for controlling diabetes and its complications. Anacardium humile is a typical plant from the Brazilian savanna used in folk medicine due to its anti-diarrheal, expectorant, anti-diabetic and anti-inflammatory properties. However, few studies address the biological properties of this species. This study aimed to analyze in vitro and ex vivo the antioxidant and antiglycant capacity of the ethanolic extract of A. humile, its organic fractions and three molecules (catechin, quercetin and gallic acid - CQA), their potential to inhibit the enzymes α-amylase and α-glucosidase, as well as their cytotoxic effects on RAW 264.7 macrophages. The adopted methodology consisted of obtaining the ethanolic extract of A. humile and its organic fractions, which were tested, together with CQA, for their antioxidant, antiglycant and glycolytic enzyme inhibitory activities. In addition, CQA and the three A. humile fractions that showed the best results in the abovementioned assays were tested for their ability to inhibit oxidation in liver tissue. Furthermore, the bioactive compounds present in the fractions of A. humile leaves were elucidated by HPLC-ESI-MS/MS analysis. The analyses showed remarkable antioxidant activity in DCM (1264.85 ± 76.90 μmol ET/g ORAC; 216.71 ± 1.04 μmol ET/g FRAP and IC50 3.03 ± 0.08 µg/mL DPPH) and AcOEt (1300.11 ± 33.04 μmol ET/g ORAC; 236.21 ± 23.86 μmol ET/g FRAP and IC50 3.03 ± 0.14 µg/mL DPPH) fractions, and in CQA, mainly in gallic acid (1291.19 ± 8.41 μmol ET/g ORAC; 1103.52 ± 31.48 μmol ET/g FRAP and IC50 0.78 ± 0.11 µg/mL DPPH). As for the antiglycant activity, the samples at the concentration of 40 μg/mL inhibited more than 88% of the glycation in the BSA/FRU method. In the BSA/MGO and ARG/MGO methods, catechin and the Hex, DCM and AcOEt fractions obtained the best results. Only CQA showed significant results in the LYS/MGO model. All fractions, except Hex, significantly inhibited the α-amylase enzyme (IC50 DCM 0.56 ± 0.10; AcOEt 0.84 ± 0.01; ButOH 0.74 ± 0.03 and H2O 0.79 ± 0.06 µg/mL). Inhibition of the α-glucosidase enzyme was only observed in the AcOEt fraction (IC50 275.40 ± 12.31 µg/mL). Tests with liver tissue revealed a notorious potential of the DCM, AcOEt and ButOH fractions, as well as CQA, to inhibit the production of ROS and lipid peroxidation, in addition to preserving thiol groups. Molecules with great antioxidant potential such as catechin, quercetin, gallic acid, kaempferol, luteolin and β-cryptoxanthin were identified in the fractions. In conclusion, the ethanolic extract fractions of A. humile present promising antioxidant and antiglycant activities, in addition to a prominent capacity to inhibit the α-amylase enzyme.Thus, this study presents new information and encourages further research to elucidate the biological properties of A. humile and its potential to control DM and its complications.